2017
DOI: 10.3390/cancers9020017
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Signaling in Salivary Gland Cancer

Abstract: Salivary gland cancers comprise a small subset of human malignancies, and are classified into multiple subtypes that exhibit diverse histology, molecular biology and clinical presentation. Local disease is potentially curable with surgery, which may be combined with adjuvant radiotherapy. However, metastatic or unresectable tumors rarely respond to chemotherapy and carry a poorer prognosis. Recent molecular studies have shown evidence of androgen receptor signaling in several types of salivary gland cancer, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 62 publications
(103 reference statements)
3
54
0
Order By: Relevance
“…Studies investigating the prognostic significance of AR positivity have shown mixed results [6, 18, 33, 49, 52]. Genetic alterations in androgen receptors noted in SDC specimens include mutations and extra gene copies, but not gene amplification as seen in prostate cancer [49, 52, 53]. Androgen receptor splice variants missing exons needed for receptor activation, in particular the AR-V7 splice variant, are expressed in a significant number of SDC specimens; these AR splice variants encode a truncated AR protein that has only the transactivating N-terminal domain without the C-terminal ligand binding domain, which results in constitutive activation of AR [52, 53].…”
Section: Mutational Landscape Of Sdcmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies investigating the prognostic significance of AR positivity have shown mixed results [6, 18, 33, 49, 52]. Genetic alterations in androgen receptors noted in SDC specimens include mutations and extra gene copies, but not gene amplification as seen in prostate cancer [49, 52, 53]. Androgen receptor splice variants missing exons needed for receptor activation, in particular the AR-V7 splice variant, are expressed in a significant number of SDC specimens; these AR splice variants encode a truncated AR protein that has only the transactivating N-terminal domain without the C-terminal ligand binding domain, which results in constitutive activation of AR [52, 53].…”
Section: Mutational Landscape Of Sdcmentioning
confidence: 99%
“…Genetic alterations in androgen receptors noted in SDC specimens include mutations and extra gene copies, but not gene amplification as seen in prostate cancer [49, 52, 53]. Androgen receptor splice variants missing exons needed for receptor activation, in particular the AR-V7 splice variant, are expressed in a significant number of SDC specimens; these AR splice variants encode a truncated AR protein that has only the transactivating N-terminal domain without the C-terminal ligand binding domain, which results in constitutive activation of AR [52, 53]. Presence of AR-V7 in circulating tumor cells has been associated with resistance to androgen deprivation therapy in prostate cancers [54], but it is unclear whether presence of AR-V7 in tumor tissue in SDC would be associated with outcome or therapeutic resistance.…”
Section: Mutational Landscape Of Sdcmentioning
confidence: 99%
See 3 more Smart Citations